2016
DOI: 10.1002/suco.201400084
|View full text |Cite
|
Sign up to set email alerts
|

Shear strength of self-compacting concrete beams with small stirrups ratios

Abstract: In comparison with a vibrated concrete (VC) of the same strength class, self‐compacting concrete (SCC) typically has a lower coarse aggregate content and, possibly, a smaller maximum aggregate size. This may result in reduced aggregate interlock between the fracture surfaces of a SCC. Since aggregate interlock plays an important role in the shear strength of slender beams, SCC beams may have a shear strength lower than that of similar VC beams, but studies on that subject are still limited. This article summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…From those beams, 54 of SCC and 11 of VC had h<300mm and 16 of SCC and 8 of VC had ρ>4%, values that do not correspond to real cases of beams and that lead to improved ultimate shear stress. Only 7 of the SCC beams had ρ w f yw close to the minimum recommended by codes of practice and high strength concrete, besides usual height value [12,15]. No beam had skin reinforcement.…”
Section: Commentaries On the Experimental Studiesmentioning
confidence: 84%
See 4 more Smart Citations
“…From those beams, 54 of SCC and 11 of VC had h<300mm and 16 of SCC and 8 of VC had ρ>4%, values that do not correspond to real cases of beams and that lead to improved ultimate shear stress. Only 7 of the SCC beams had ρ w f yw close to the minimum recommended by codes of practice and high strength concrete, besides usual height value [12,15]. No beam had skin reinforcement.…”
Section: Commentaries On the Experimental Studiesmentioning
confidence: 84%
“…Considering the shear database for VC beams without shear reinforcement of Reineck et al [23] and their SCC tested beams, Arezoumandi and Volz [20] concluded that there is no statistically significant difference between the ultimate normalized shear stress of VC and SCC beams. Resende, Shehata and Shehata [12] aimed to investigate the shear behaviour of high strength SCC beams and small amounts of shear reinforcement, case that had not been studied (only one beam with small value of ρ w f yw and f c ≈54MPa had been tested by Cuenca, Serna and Pelufo [15]). The six beams tested were produced with a SCC provided by a ready-mixed concrete supplier that had been used in a cast-in-place structure.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations